2017
DOI: 10.1159/000479925
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relation between Vitamin D and Interleukin-17 in Vitiligo? A Cross-Sectional Study

Abstract: Background: High interleukin (IL)-17 contributes to vitiligo pathogenesis. Vitamin D has been assessed in vitiligo, with no reports targeting its relation to IL-17. Objective: To evaluate a possible regulatory effect of vitamin D on IL-17 and their relation to disease activity in vitiligo. Methods: This study included 30 vitiligo patients and 40 controls evaluated for IL-17 and vitamin D serum levels by ELISA technique. Results: IL-17 was significantly higher (p = 0.001) whereas vitamin D was found to be lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 19 publications
1
20
1
2
Order By: Relevance
“…Of initially identified 165 citations, 11 studies including 626 vitiligo patients and 475 controls were finally selected . The study selection process using PRISMA flow chart is shown in Figure , and the characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of initially identified 165 citations, 11 studies including 626 vitiligo patients and 475 controls were finally selected . The study selection process using PRISMA flow chart is shown in Figure , and the characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A link between IL‐17 levels and the extent of body surface involvement has been reported. Variable results were published regarding their association with disease activity (Abdallah et al, ; Aly et al, ; Basak, Adiloglu, Ceyhan, Tas, & Akkaya, ; Bhardwaj, Rani, Srivastava, Kumar, & Parsad, ; Elela, Hegazy, Fawzy, Rashed, & Rasheed, ).…”
Section: Characteristics and Clinical Evolution Of The Patients In Thmentioning
confidence: 99%
“…The available studies in the literature are inconsistent on Vit-D levels and Hypovitaminosis D is still controversial in vitiligo. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 In this updated systematic review and meta-analysis on vitiligo and Vit-D levels (ViViD Study), the serum Vit-D levels and their association with variables like age, disease duration, affected Body Surface Area (BSA), and Vitiligo Activity and Severity Index (VASI) were studied in vitiligo patients as compared to controls. A subgroup meta-analysis was conducted to study Vit-D levels in relation to gender, skin type, Vitiligo type, disease activity, vitiligo history, autoimmune comorbidities, and indoor-outdoor job status of vitiligo patients.…”
Section: Introductionmentioning
confidence: 99%